A comprehensive review of Flywheel Energy Storage System technology. (January 2017) - Mousavi G, S.M.; Faraji, Faramarz; Majazi, Abbas; Al-Haddad, Kamal
Abstract: Energy storage systems (ESSs) play a very important role in recent years. Flywheel is one of the oldest storage energy devices and it has several benefits. Flywheel Energy Storage System (FESS) can be applied from very small micro-satellites to huge power networks. A comprehensive review of FESS for hybrid vehicle, railway, wind power system, hybrid power generation system, power network, marine, space and other applications are presented in this paper. There are three main devices in FESS, including machine, bearing, and Power Electronic Interface (PEI). Furthermore, advantages and disadvantages all of them have been presented. In addition a brief review of new and conventional power electronic converters used in FESS, have been discussed. Finally, practical ways to develop this technology in the future are presented.